Microbiology and antimicrobial effects of kombucha, a short overview - İÇEN, HAYRUNİSA; OMURTAG KORKMAZ, BURCU İREM (My University, 2023)
Kombucha is a beverage usually prepared with black or green tea containing sucrose, and a synbiotic culture of bacteria and yeasts (SCOBY). This paper aims at offering an overview on kombucha microbiota, as well as on its nutritional composition, and antimicrobial effects. The microbiota of kombucha includes acetic acid bacteria (Acetobacter, Gluconobacter, Gluconacetobacter, Komagataeibacter), lactic acid bacteria (Lactobacillus, Lactiplantibacillus, Lacticaseibacillus) and yeasts (Brettanomyces, Candida, Saccharomyces, Zygosaccharomyces), depending on raw materials, starter cultures, and fermentation temperature. The second topic of this review is the production path and kombucha composition, with a synopsis from a quali-quantitative point of view of the most important compounds. Finally, the review examines the antimicrobial potential, focusing on both Gram-positive and Gram-negative bacteria. An open question is on the probiotic status of kombucha; this review offers a contribution to this debate, suggesting for this beverage the status of post-biotic.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Yaşam Bilimleri (LIFE); Tarım Bilimleri; GIDA BİLİMİ VE TEKNOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Agriculture & Environment Sciences (AGE); Life Sciences (LIFE); AGRICULTURAL SCIENCES; MOLECULAR BIOLOGY & GENETICS; FOOD SCIENCE & TECHNOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yemek bilimi; Biyokimya; Food Science; Biochemistry; Antimicrobial effect; Fermentation; Microbiota; Nutrition